Teaching young children : - Henniger, Michael L. (Prentice Hall, 2009)
Appropriate for courses in Introduction to Early Childhood Education. Exceptionally lively, practical, and reader-friendly, this introduction to early childhood education text is unique because of its focus on the value of play. Strong coverage of child development, as well as thoughtful discussions about guiding young children, working with families, and celebrating diversity will help teachers facilitate all aspects of the 0-to-8-year-old child's physical, social/emotional, and intellectual growth. The text also includes an overview and concise history of the field, information on professional development, and clear explanations of theoretical foundations for early childhood education. Chapters on curriculum in the areas of mathematics, science, social studies, language and literacy, and the creative arts show teachers how to link theory to classroom practice, making this comprehensive and engaging textbook particularly useful